PEMANFAATAN KECERDASAN BUATAN DALAM MENGEMBANGKAN DAKWAH DIGITAL - Soffiyana Dwi Jupriyanti; Nur Fitriyani; Fauzia Nur Aeni; Muhammad Rikzam Kamal (Jurnal Komunikasi dan Media, 2025)
This study was conducted to see how artificial intelligence is utilized in developing digital da'wah content. The main focus of this study is to understand how artificial intelligence (AI) is utilized in developing digital da'wah content and to identify the challenges faced by artificial intelligence (AI) in digital da'wah. The method used in this study is the Systematic Literature Review (SLR). The SLR approach is applied to find, evaluate, and interpret all relevant research related to interesting phenomena in this topic, with an emphasis on appropriate research questions. By applying the SLR Method, journals can be analyzed and identified systematically, following the steps or protocols that have been set at each stage. The results of the study show that based on the SLR Method, the Artificial Intelligence/Chatbot that is most widely studied by researchers focuses on Websites and AI Applications. In addition, the most common challenges faced are ethical issues and data privacy security.